2014
DOI: 10.1088/0953-8984/26/30/306002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental percolation studies of two-dimensional honeycomb lattice: Li2Mn1–xTixO3

Abstract: Li 2 MnO 3 with a S=3/2 two-dimensional Mn honeycomb lattice has a Neel-type antiferromagnetic transition at T N =36 K with a broad maximum in the magnetic susceptibility at T M =48 K. We have investigated site percolation effects by replacing Mn with nonmagnetic Ti, and completed a full phase diagram of Li 2 Mn 1-x Ti x O 3 solid solution systems to find that the antiferromagnetic transition is suppressed continuously without a clear sign of changes in the Neel-type antiferromagnetic structure. The magnetic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(70 reference statements)
2
5
0
Order By: Relevance
“…The paramagnetic-to-antiferromagnetic transition temperature (in Figure b) almost linearly decreases upon increasing dopant concentration, changing by about 24% from x = 0 to 0.1. The doping-induced drop in the transition temperature agrees with the percolation theory . Additionally, the Curie tail or susceptibility upturn at low temperatures gradually increases due to the disordered spins near the nonmagnetic Cd atoms embedded in the background of the original collinear-ordered states.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The paramagnetic-to-antiferromagnetic transition temperature (in Figure b) almost linearly decreases upon increasing dopant concentration, changing by about 24% from x = 0 to 0.1. The doping-induced drop in the transition temperature agrees with the percolation theory . Additionally, the Curie tail or susceptibility upturn at low temperatures gradually increases due to the disordered spins near the nonmagnetic Cd atoms embedded in the background of the original collinear-ordered states.…”
supporting
confidence: 76%
“…The doping-induced drop in the transition temperature agrees with the percolation theory. 12 Additionally, the Curie tail or susceptibility upturn at low temperatures gradually increases due to the disordered spins near the nonmagnetic Cd atoms embedded in the background of the original collinear-ordered states. As aforementioned, the extremely narrow and high-intensity peak is key evidence for the coherent phenomena from the simultaneous dipole transition of the local NiS 6 clusters.…”
mentioning
confidence: 99%
“…At the NN honeycomb lattice percolation threshold, a shift in the slope of the transition temperature was observed, which was attributed to a loss of dependence on the NN interactions. In their study of replacing Mn with Ti in Li 2 MnO 3 , Lee et al reported that the percolation threshold in this system is 0.7, suggesting that there are contributions of up to third nearest neighbors [14]. There have been a few theoretical studies in this direction as well.…”
Section: Introductionmentioning
confidence: 96%
“…Magnetic dilution has been studied in MnPS 3 as well as Li 2 MnO 3 . Both these compounds are made up of honeycomb layers, in which spins are coupled antiferromagnetically within the plane [13,14]. In their study of diluting MnPS 3 by replacing Mn with Zn, Goossens et al reported that the percolation threshold of the material was 0.55 instead of the 0.3 expected for a NN honeycomb lattice [13].…”
Section: Introductionmentioning
confidence: 99%
“…A quantum Monte Carlo study also suggested that a quantum spin liquid state might emerge if the honeycomb system was located in the intermediate correlation regime where the carriers are partially localized [11]. A percolation study of Li 2 Mn 1−x Ti x O 3 indicated that the further-neighbor interactions were not negligible: the evolution of the magnetic ground state can be described well when one considers up to the third nearest-neighbor interactions [12]. The release of a significant amount of magnetic entropy above T N , which is usually seen in systems with strong frustration, further suggests the presence of magnetic frustration in Li 2 MnO 3 [9].…”
Section: Introductionmentioning
confidence: 99%